Optimasi Formula Sediaan Tablet Getah Kuning Tanaman Ashitaba (Angelica Keiskei) Dengan Kombinasi Starlac® Dan Kalsium Fosfat Dibasik Menggunakan Metode Desain Faktorial - Wacana, Alfi Octavianingrum; , Suprapto, M.Sc., Apt (2016)
Ashitaba plant (Angelica keiskei) yellow sap have a compound called 4- Hydrooxyderrixcine which can reducing blood glucose level. Formulation Ashitaba sap into tablet dosage is expected to increase benefits and effects. This study aims to determine the effect of the combination of StarLac® and dibasic calcium phosphate at the physical properties of the tablet Ashitaba plant yellow sap tablet, as well as to obtain the optimum formula. Tablets was made by using wet granulation method. Combination StarLac® and Dibasic Calcium Phosphate for FI (6% : 6%), FII (6% : 24%), FIII ( 24% : 6%), dan FIV (24% : 24%). The exipients are microcrystalin celulose, methyl paraben, talc, magnesium stearate, sodium alginate and aerosil. The flow rate of granules, tablets uniformity, hardness, friability and disintegration time were examined. Analysis of the data to obtain optimum prediction formula using Design Expert software. Results of prediction and verification testing by t-test statistics. The results showed a high level StarLac® dominant factor to the improvement of the flow properties of the granules, lowers CV weight uniformity, and reduce the tablet hardness, while the factors of high levels of dibasic calcium phosphate dominant to increase friability and disintegration time becomes faster. There are five areas that the optimum formula can be selected based Design Expert. One optimum combination StarLac® and dibasic calcium phosphate 2 obtained was 65.65 mg and 30 mg, or 13% and 6%. The combination is chosen to be the optimum formula because it has a value greater desirability is 0,367. Keywords: Ashitaba, Angelica keiskei, tablet, StarLac®, dibasic calcium phosphate.